AVALIAÇÃO DA ESTABILIDADE DAS ALTERAÇÕES TRANSVERSAIS PROMOVIDAS PELO APARELHO REGULADOR DE FUNÇÃO FRANKEL 2, POR MEIO DE TELERRADIOGRAFIAS POSTEROANTERIORES - Margreiter, Sissiane (2010)
The purpose of this study was to evaluate, through posteroanterior cephalometric measurements, the transverse alterations promoted by functional regulator Frankel 2 appliance in patients with Class II, division 1 malocclusion, and check the stability after a average of 7,11 years after treatment. The sample included a total of 45 posteroanterior radiographs from 15 patients treated with RF-2 appliance therapy, carried out in three phases: (T1) start of treatment; (T2) end of treatment and (T3) post-treatment. Other 36 were evaluated posteroanterior cephalograms of untreated patients that represent the control group, in two phases: (T1) and (T2). The radiographs were scanned and it was used a software Radiocef 2 to make cephalometric measurements. To compare the changes in the initial, final and posttreatment in the treated group was employed analysis of variance followed by Tukey multiple comparison test (p<0,05). The results showed that during the treatment period the increase lower and upper intermolars increased and were statistically significant. Longer distances that represent the width of the nasal cavity, lower facial height, width and distance of lower intermolar lower jaw did not change statistically significant. In the post-treatment, there was a mild reduction in lower and higher intercanine and intermolar distances. However, considering the changes due to growth and development of dental arches cross over this period, there would be a reduction in these distances, there was probably a relative stability of dental changes promoted by transverse RF-2. Therefore, it can be concluded that the RF-2 has no effect skeletal cross. However, there is an increase in upper and lower intermolar intercanine distance during treatment, which remains relatively stable, considering the changes in the normal growth and development of dental arches.